The Effect Of Work Family Conflict On Employees' Career Development Is Moderated By Length Of Work at PT. Jiwasraya Medan Branch - Harasifa, Meggy; Ambari, Safira (Cattleya Darmaya Fortuna, 2024)
From the initial research that the researchers conducted, the phenomenon in the company was the large number of workers who were still preoccupied with work outside the company compared to the work carried out inside the company, conflicts often occurred in someone who worked outside the home, both domestic conflicts and internal conflicts. work. Where an employee feels demanded to be a father or mother for his child, wife or as a husband at home, without knowing the time and how an employee must stick to his commitment in work or organization as a worker. The purpose of this study was to determine the effect of work family conflict on employee career development, to determine the effect of work family conflict on length of work and to determine whether the duration of work has an effect on work family conflict. The number of samples in this study amounted to 116 people using saturated sample techniques. The analysis technique used is multiple linear regression and MRA. The results of the study show that work family conflict, length of employment of employees, and career development affect simultaneously (together). The duration of work does not moderate the relationship between work family conflict with employee career development or the duration of work is not a moderating variable.